Cough frequency in children with stable asthma: correlation with lung function, exhaled nitric oxide, and sputum eosinophil count. Issue 11 (29th October 2003) - Li, A M; Lex, C; Zacharasiewicz, A; Wong, E; Erin, E; Hansel, T; Wilson, N M; Bush, A
Abstract : Background: A study was undertaken to assess the correlation between cough frequency in asthmatic children with lung function and two non-invasive markers of airway inflammation. Methods: Thirty two children of median age 12.0 years (interquartile range (IQR) 9.5–13.4) with stable asthma were recruited. They underwent spirometric testing, exhaled nitric oxide (eNO) measurement, sputum induction for differential cell count, and ambulatory cough monitoring over 17 hours and 40 minutes. Coughing episodes were counted both as individual spikes and as clusters. Results: Complete cough frequency data were available in 29 children (90%) and their median forced expiratory volume in 1 second (FEV1 ) and eNO were 88.5% (IQR 79.5–98) and 23.9 ppb (IQR 11.4–41.5), respectively. The median number of cough episodes was 14 (IQR 7.0–24.0) which was significantly higher than that of normal children (6.7 (IQR 4.1–10.5), p<0.001). Sputum induction was successful in 61% of the subjects; the median induced sputum eosinophil count was 0.05% (IQR 0–9.0). Cough frequency was found to have a significant positive correlation with eNO (Spearman's r =0.781, p<0.001) but not with FEV1 or sputum eosinophil count ( r =−0.270, p=0.157; r =0.173, p=0.508, respectively). Conclusions: Children with stable asthma have increased cough frequency compared with normal controls and cough frequency was greater during the day than at night. Cough may be a more sensitive marker of airway inflammation than simple spirometry.